CURRICULUM MODIFICATIONS TO CREATE AN INCLUSIVE LEARNING ENVIRONMENT IN A REGULAR CLASSROOM FOR STUDENTS WITH DYSTONIC CEREBRAL PALSY AND CHOREOATHETOSIS: A CASE STUDY (Proceedings of the International Conference on Education, 2025)
This case study investigates curriculum modifications designed to foster an inclusive learning environment for students with dystonic cerebral palsy and choreoathetosis, focusing on a 10-year-old student, "Ali" (a pseudonym), in a mainstream classroom in Sharjah, UAE. The study employs a qualitative methodology involving observations, interviews, and document analysis to understand how tailored educational strategies address Ali’s academic, social-emotional, and motor development needs. Key interventions include leveraging assistive technologies, adapting teaching methods, and implementing individualized educational plans (IEPs) aligned with the UAE's inclusive education policies. While Ali benefited from social inclusion and personalized learning support, challenges emerged, including teachers' limited training in inclusive practices, inconsistent curriculum adjustments, and resource constraints. Observations revealed that while technology integration in English and mathematics enhanced learning, activities requiring prolonged writing posed difficulties. Despite these hurdles, Ali progressed in social interaction, group participation, and specific academic tasks. The study emphasizes the need for professional development to equip teachers with the skills to deliver inclusive education effectively. Recommendations include further customization of curricula, increased use of assistive technology, and fostering collaborative partnerships among educators, parents, and inclusion specialists. This research underscores the importance of aligning educational practices with legal mandates and addressing the unique needs of students with disabilities to ensure equitable learning opportunities.
Keywords: inclusive education; curriculum modifications; dystonic cerebral palsy; assistive technology; individualized educational plans (IEPS); social integration